1984
DOI: 10.1007/bf00546700
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of changes in the characteristics of ?-adrenoceptors and responsiveness of human circulating lymphocytes during and after chronic administration of pindolol and propranolol

Abstract: The characteristics of the beta-adrenoceptors (3H-dihydroalprenolol binding) and the beta-adrenergic responsiveness (cyclic AMP response to isoproterenol) were studied in circulating lymphocytes from healthy volunteers before (D 0), on the 22nd day of treatment (D 22) and on the fifth day (D 30) following discontinuation of pindolol 15 mg/day or propranolol 160 mg/day. During pindolol therapy (D 22) the beta-adrenoceptor-affinity towards dihydroalprenolol was unchanged and the beta-adrenoceptor density decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…On the other hand, 0.3 mg/kg carteolol (which is nearly equipotent to 30 mg/kg propranolol) had no effect on /8 adrenoceptors in SHR heart, and 10 mg/kg carteolol decreased the number of a-adre noceptors in SHR heart without significant changes in the Kd values. Our results are in agreement with those of other investigators who suggested that the "rebound phenomena" after withdrawal would not occur following /3 adrenoceptor antagonists with ISA (8)(9)(10). In WKY, we observed a significant increase in heart rate at 10 weeks following 10 mg/kg car teolol (16-week old), suggesting that the ISA was actually acting in carteolol-treated WKY.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, 0.3 mg/kg carteolol (which is nearly equipotent to 30 mg/kg propranolol) had no effect on /8 adrenoceptors in SHR heart, and 10 mg/kg carteolol decreased the number of a-adre noceptors in SHR heart without significant changes in the Kd values. Our results are in agreement with those of other investigators who suggested that the "rebound phenomena" after withdrawal would not occur following /3 adrenoceptor antagonists with ISA (8)(9)(10). In WKY, we observed a significant increase in heart rate at 10 weeks following 10 mg/kg car teolol (16-week old), suggesting that the ISA was actually acting in carteolol-treated WKY.…”
Section: Discussionsupporting
confidence: 92%
“…Several investigators found that in human lymphocytes, chronic treatment with proprano lol led to an increase in the number of /3 adrenoceptors, while chronic treatment with ,Q-adrenoceptor antagonists with intrinsic sym pathomimetic activity (ISA) did not lead to an increase (but rather led to a decrease) in the number of /3-adrenoceptors (8)(9)(10). Based on these results, they suggested that "rebound phenomena" could be prevented by the use of /3-adrenoceptor antagonists with ISA.…”
mentioning
confidence: 99%
“…These receptors do not seem to be downregulated in the hearts of patients in failure (Bristow, 1989). The nonselective beta-blocker propranolol causes upregulation of lymphocyte receptors [50][51][52], whereas the nonselective compound pindolol with ISA causes downregulation [50,52,53]. Acebutolol, a betal-selecrive ISA drug, does not induce downregulation in lymphocyte receptors [53].…”
Section: Possible Mechanisms By Which Beta-blockers May Be Beneficialmentioning
confidence: 99%
“…Perkins et al (198 1) have demonstrated that P-adrenoceptor agonists, but not antagonists, can initiate the process of desensitization. However, it was recently observed that chronic therapy with pindolol, a P-adrenoceptor antagonist with intrinsic sympathomimetic activity, induced a P-adrenoceptor desensitization in human lymphocytes (Giudicelli et al 1984). Whether prenalterol which can act as both an agonist and an antagonist behaves in the same way in this respect during long-term treatment, remains to be demonstrated.…”
mentioning
confidence: 99%